Filtración glomerular aplicando a la Fórmula de Cockcroft y Gault a pacientes diabéticos tipo 2 e hipertensos atendidos en consulta externa del Hospital Teófilo Dávila de julio - septiembre del 2009 - Sánchez Prado, Einer D. (2010)
A good performance of renal system is one of the most important biologicals processes for the conservation of the internal meddle and essential for a good condition of health. Whit the objective of evaluate the renal function through the glomerular filtration index (IFG) by means Cockcroft and Gault formula is realized an observational descriptive study in 200 elders patients of 30 years whit diagnostic of type 2 diabetes mellitus and hypertension arterial in the area of external consultation of Teófilo Davila´s of the city Machala.